Rediscovering CPET: the prognostic value of hemodynamic gain index in heart failure. (3rd October 2022) - Borges-Rosa, J; Martinho, S; Almeida, J P L; Milner, J; Oliveira-Santos, M; Goncalves, L
Abstract: Introduction: Cardiopulmonary exercise testing (CPET) is recommended in patients with heart failure (HF) to optimize exercise prescription and as part of the evaluation for heart transplantation. Hemodynamic gain index (HGI) derived from CPET has been proposed as a new marker of risk stratification in general population cohorts. Purpose: We aimed to evaluate the prognostic value of HGI in patients with HF. Methods: We conducted a single-centre study assessing consecutive patients with HF who underwent CPET from 2013 to 2017. HGI was calculated based on heart rate (HR) and systolic blood pressure (SBP): HGI = [(HRpeak × SBPpeak) − (HRrest × SBPrest)] / (HRrest × SBPrest). Classic and recently proposed variables were collected, including peak O2 uptake (pVO2), minute ventilation–CO2 production (VE/VCO2 slope), circulatory power (CP = pVO2 × peak SBP), and ventilatory power (VP = peak SBP/(VE/VCO2) slope). The primary outcome was a composite of HF hospitalization, heart transplant, and all-cause mortality. Results: A total of 212 patients (mean age 55.4±10.9, 76.9% male) were included. Most patients had dilated cardiomyopathy (43.9%) followed by ischaemic aetiology (38.7%), with a mean left ventricle ejection fraction of 29±13%. The most used exercise protocol was the modified Naughton (76.6%), followed by the original Naughton (18.7%), and Bruce (4.8%). Mean pVO2 was 16.7±5.9mL O2 kg –1 min –1 and median VE/VCO2 slope was 37.5 [32.7–44.3]. Mean VP was 3.46±1.31mmHg while median CP was 1927 [1427–2697]mmHg min/mL/kg. Mean HGI was 0.90±0.5 bpm/mmHg. Despite weak, there were significant positive correlations between HGI and mean pVO2 (rs=0.55, p<0.01), VP (r=0.60, p<0.01), and CP (rs=0.68, p<0.01), but negative correlation between HGI and VE/VCO2 slope (rs=−0.45, p<0.01). HGI was grouped by terciles: T1 (<0.59), T2 (0.59–1.02), and T3 (>1.02). After a median follow-up of 71 [49–81] months, the primary outcome occurred in 66.0% of patients (rehospitalization, heart transplant, and all-cause death occurred in 56.1%, 25.9%, and 32.5%, respectively). In the T1 group, the multivariable-adjusted odds ratio (OR) for the primary outcome was 3.73 (95% CI 1.97–7.06, p<0.01) compared to the T3. In the T2 group, the multivariable-adjusted OR for the primary outcome was 0.47 (95% CI 0.27–0.81, p<0.01) compared to T1. There were no significant differences between T2 and T3 groups. Kaplan-Meier estimates of primary outcome during follow-up according to HGI tercile are shown in Figure 1. Conclusion: HGI is inversely associated with the composite of HF hospitalization, heart transplant, and all-cause mortality in patients with heart failure, enhancing the role of CPET in risk stratification. Funding Acknowledgement: Type of funding sources: None.